2013
DOI: 10.1590/s2317-17822013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre taxa de elocução e descontinuidade da fala na taquifemia

Abstract: OBJETIVO: Correlacionar a taxa de elocução com as rupturas da fluência em pessoas com taquifemia e comparar com pessoas sem taquifemia. MÉTODOS: Participaram dessa investigação 14 indivíduos na faixa etária de 8 a 40 anos e 11 meses de idade, de ambos os gêneros, divididos em dois grupos pareados por idade e gênero. O GI foi composto por sete pessoas com taquifemia e o GII por sete pessoas sem taquifemia. Um protocolo de avaliação da fluência da fala foi utilizado para obter e analisar a amostra de fala, que c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Disfluencies were produced the most frequently in the task of maximum speech rate which indicates that lack of time influences language planning difficulties in cluttered speech. Similarly to these results, De Oliveira et al (2013) found higher frequency of disfluencies as speech rate increased. The results also confirm the theory of Van Zaalen (2009) that PWC are not capable of adequately adjust their speech rate to the demands of the speaking situation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Disfluencies were produced the most frequently in the task of maximum speech rate which indicates that lack of time influences language planning difficulties in cluttered speech. Similarly to these results, De Oliveira et al (2013) found higher frequency of disfluencies as speech rate increased. The results also confirm the theory of Van Zaalen (2009) that PWC are not capable of adequately adjust their speech rate to the demands of the speaking situation.…”
Section: Discussionsupporting
confidence: 78%
“…Bóna (2012) studied the speech of a clutterer in four different speaking styles and the results confirmed earlier findings, that more pauses but fewer other disfluencies and phonological inaccuracies occurred when the clutterer slowed down his speech. As reported by De Oliveira et al (2013), a greater frequency of typical disfluencies was produced as speech rate increased.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, others expressed higher values than the normative data, confirming previous studies [3][4][5][6]8 . This finding supports the literature, considering that cluttering clinical aspect is heterogeneous 13 .…”
supporting
confidence: 88%
“…: speech rate 3,4,7,8 and decreased intelligibility 4 . It is also believed that there is an interaction between these manifestations, for example, rapid speech rate could provide insufficient time for the speaker to organize and make the emissions, thereby increasing the amount of speech disfluency…”
mentioning
confidence: 98%